PREDATORY POTENTIAL OF ARANEAE AGAINST APHIDIDAE PESTS IN CANOLA CROP - 1R. Amjad; 1T. Ruby; 3T. Hussain; 3 M. Rafay; 4M. Abdullah; I. Bibi; 3S. Khalil; 5S. Akhter; 5M. A. Farooqi (Journal of Animal and Plant Sciences, 2021)
The dominant spider species of order Araneae include Oxyopes javanus (Family Oxyopidae), Araenidae spp. (Family Araenidae), Pardosa oakleyi and Hippasa partita (Family Lycosidae) at cotton-wheat zone were studied for their predatory potential against three aphid species of canola crop under laboratory experiment. For laboratory experimentation, three species of aphids viz. Lipaphis erysimi, Myzus persicae, Brevicoryne brassicae, and worms were used. The results showed that spider consumed all the preys with different proportions offered in multiple and single prey feeding experiments. Oxyopes javanus was ravenous predator followed by Aranidae spp. on foliage and Pardosa oakleyi and Hippasa partita on ground with female consumed high number of preys as compared to male. Field observation showed seasonal variation in aphid population which in turn affect the diet of predators. The present study suggest that dominant spider species consumed aphids when they are at peak which may help in containing aphid population and this results in successful pest management in canola crop.
Keywords: Canola; Aphids; Spiders; Predator; Pest